The Importance of Attention to Language in the Age of Globalization - Ashurova Feruza Axmatovna (Genius Journals, 2023)
The article discusses the issues of increasing the prestige and status of the Uzbek language, the fact that the language is the main means of communication, and the positive and negative aspects of word acquisition. It was emphasized that the learning of foreign languages by young people should not be at the expense of neglecting our mother tongue
Keywords: national pride; national pridemeans of communication; raral